Tris-{Hydridotris(1-pyrazolyl)borato}lanthanide Complexes: Synthesis, Spectroscopy, Crystal Structure and Bonding Properties - Christos Apostolidis; Attila Kovács; Alfred Morgenstern; Jean Rebizant; Olaf Walter (Inorganics, 2021)
Complexes of trivalent lanthanides (Ln) with the hydridotris(1-pyrazolyl)borato (Tp) ligand Ln[η3-HB(N2C3H3)3]3 (LnTp3) were subjected to a joint experimental–theoretical analysis. X-ray diffraction experiments have been performed on CeTp3, NdTp3, SmTp3, GdTp3, and TbTp3 in the nine-fold coordination and on DyTp3, HoTp3, ErTp3, TmTp3, YbTp3, and LuTp3 in the eight-fold coordination form. Density functional theory (DFT) calculations were carried out for all 15 LnTp3 complexes. They extended the X-ray diffraction data available on the LnTp3 compounds and facilitated a straightforward interpretation of trends in the structural parameters. As a result of the joint analysis, significant steric strain in the equatorial coordination sites of the nine-coordinate structures was recognized. Trends in the bonding properties were elucidated by energy decomposition and quantum theory of atoms in molecules (QTAIM) analysis of the electron density distribution. These results revealed the major electrostatic character of the Ln…Tp bonding and fine variation of charge transfer effects across the Ln row.